Artificial pupil versus contralateral balanced contact lens fit for presbyopia correction - García-Lázaro,Santiago (2014)
Purpose: To assess and compare the effects of contact lens-based artificial pupil design and contralateral balanced multifocal contact lens combination (CBMCLC) on visual performance. Methods: This randomized crossover study conducted at the University of Valencia, Spain included 38 presbyopic patients using an artificial pupil contact lens in the nondominant eye and a CBMCLC. After a month of lens wear, the binocular distance visual acuity (BDVA), binocular near visual acuity (BNVA), defocus curve, binocular distance, and near contrast sensitivity and near stereoacuity (NSA) were measured under photopic conditions (85 cd/m2). Moreover, BDVA and binocular distance contrast sensitivity were examined under mesopic conditions (5 cd/m2). Results: Visual acuity at an intermediate distance and near vision was better with the CBMCLC than with the artificial pupil (p<0.05). Statistically significant differences were found in contrast sensitivity between the two types of correction for distance (under mesopic conditions) and for near vision, with the CBMCLC exhibiting better results in both cases (p<0.05). The mean NSA values obtained for the artificial pupil contact lens were significantly worse than those for the CBMCLC (p=0.001). Conclusion: The CBMCLC provided greater visual performance in terms of intermediate and near vision compared with the artificial pupil contact lens.